1999
DOI: 10.1002/j.1550-8528.1999.tb00410.x
|View full text |Cite
|
Sign up to set email alerts
|

Dermatoses in 156 Obese Adults

Abstract: TOPETE, JORGE GONZALEZ-BARRANCO, ANTONIO R. VILLA, JOSE J. DALMAN, AND GUADALUPE OR-TIZ-PEDROZA. Dermatoses in 156 obese adults. Obes Res.Background: Skin diseases are mentioned as a frequent finding in the obese patient. However, to our knowledge no study has been done on this subject. Objective: To determine the prevalence of skin diseases associated with different obesity grades and if any dermatosis can be considered an obesity marker. Materials and Methods: A cross-sectional study of 156 obese patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
74
4
27

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(112 citation statements)
references
References 11 publications
7
74
4
27
Order By: Relevance
“…The most common dermatological finding observed in the study was acanthosis nigricans seen in 64.44%, similar to studies by Hud et al [ , 4] Garcia-Hidalgo et al [5] . the incidence of acanthosis nigricans increased with increasing BMI similar to Hud et al , Katz et al [6] and Burke et al [7] studies.…”
Section: Discussionsupporting
confidence: 90%
“…The most common dermatological finding observed in the study was acanthosis nigricans seen in 64.44%, similar to studies by Hud et al [ , 4] Garcia-Hidalgo et al [5] . the incidence of acanthosis nigricans increased with increasing BMI similar to Hud et al , Katz et al [6] and Burke et al [7] studies.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the frequency of acrochordon was significantly higher in obese patients, but there was no statistically significant difference between patients with and without insulin resistance. Thus, our results do not support the findings of Kahana et al 19 , but they support the findings of Garcia-Hidalgo et al 10 . In addition, we found that the mean age of patients with acrochordon was higher in both groups, although there was no significant difference.…”
Section: Resultscontrasting
confidence: 99%
“…The plantar hyperkeratosis may be regarded as a physiologic response to mechanical trauma 9 and hyperkeratosis of the soles in obesity was first described by Garcia-Hidalgo et al in 1999 10 . It was reported that obese patients showed increased forefoot width and higher plantar pressures during standing and walking in study of Hills et al 11 Because of this, we think that plantar hyperkeratosis is an expected finding in obesity.…”
Section: Resultsmentioning
confidence: 99%
“…Bir başka çalışmada ise 156 obez hastanın 69'unda akrokordon saptanmış ve VKİ ile akrokordon sayısı iliş-kili bulunmuştur. 15 Çalışmamızda da obez ve aşırı kilolularda kontrol grubuna göre anlamlı olarak daha fazla akrokordon görüldü. Ancak akrokordon varlığını muhtemelen bir derecelendirmeye tabi tutmadığımız-dan aşırı kilolu ve obez grup arasında bir fark tespit edemedik.…”
Section: Discussionunclassified
“…Garcia-Hidalgo ve ark. 15 akantozis nigrikans sıklığını VKİ 27-35 kg/m 2 olan hasta grubunda %14,7-17,9, VKİ 40 ve üzeri olan hastalarda ise %40'ın üzerinde bulmuşlardır. Ayrıca Hud ve ark.…”
Section: Discussionunclassified